Effects of Horizontal Deficiency Location on the Structural Behaviors of Steel SHS Short Columns Strengthened using CFRP - Amin Shabani Ammari; Kambiz Narmashiri (Mechanics of Advanced Composite Structures)
Several deficient steel structural members require to be strengthened all over the world. In this article, horizontal defects were generated at three locations (top, middle, and bottom) on the middle element and the middle of the side element. Consequently, the effects of the location of such defects on axial behavior of Carbon Fiber Reinforced Polymer (CFRP) strengthened steel Square Hollow Section (SHS) tubular short columns were examined. To this end, a total of 13 steel columns were experimentally examined. The same specimens were simulated applying ABAQUS V.6.14. The samples were no defect (control), 6 non-strengthened columns with defects at different locations, and 6 strengthened specimens with defects. The results indicated that horizontal defects caused a significant decrease in load bearing capacity and initial performance. The damage located at the middle and the middle of the corner elements caused the most reductions on load bearing capacity by 16% and 17%, compared to the control, respectively. The defects on the side element led to greater destruction and bearing capacity decline compared to the middle defects. As a result of axial loading, the area of horizontal defects experienced local buckling, lateral rupture, and axial deformation boost. Carbon Fiber played a key role in ductility and strength increase around the defect by covering it. Applying four CFRP layers declined the stress concentration, delaying the local buckling as a result of high confining strength. The fiber increased bearing capacity by 64% and 37% for the middle and the corner elements, compared to the control.